Dandy– Walker Malformation in a Multiparous Woman: A Case Report - Afdanil, Fitra; Suhaimi, Donel (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Background: Dandy-Walker malformation (DWM) or syndrome is a posterior fossa anomaly characterized by agenesis or hypoplasia of the vermis and cystic enlargement of the fourth ventricle causing upward displacement of the tentorium and torcula characterized by dilated posterior fossa, cystic enlargement of the fourth ventricle, hypoplasia of cerebellar vermis and its upward rotation. Most patients have hydrocephalus at the time of diagnosis.Case presentation: A 36-years-old multiparous woman with 39 weeks’ gestation from obstetrics polyclinic with plan for induction of labor. During an ultrasound examination, the fetomaternal department found congenital abnormalities in the fetus, namely the presence of hydrocephalus accompanied by Dandy-Walker syndrome. The patient denied the consumption of alcohol, usage of cosmetic drugs such as isotretinoin or blood thinning drugs. The patient previously had a sudden fever without reddish rash for 7 days at 6 months of gestation which healed on its own. The patient admitted to keeping a cat at her house since last year. The patient admitted that she had never had her blood checked for TORCH screening. After being done of Cervical ripening with Misoprostol according to FIGO 25 mcg/PV/6 hours, born a live baby girl, BW 2440 gr, BL 46 cm, A/S: 6/8.Conclusions: The patient was admitted to the hospital with the main complaint of G4P3A0L3 Gestational age 39-40 weeks, not in labor and a live single fetus in the womb, the patient’s head presentation from the obstetrics clinic with intermittent episodes of vomiting, headache with plans for induction of labor with ultrasound results of Dandy-Walker Syndrome. Pregnant women with DWS in foetal ultrasonic examination should be offered a careful and comprehensive foetal ultrasound scan and further prenatal genetic testing.Malformasi Dandy-Walker pada Wanita Multipara: Laporan KasusAbstrakLatar Belakang: Malformasi atau sindrom Dandy-Walker (DWM) merupakan anomali fosa posterior yang ditandai dengan agenesis atau hipoplasia vermis dan pembesaran kistik ventrikel keempat yang menyebabkan perpindahan tentorium dan torkula ke atas yang ditandai dengan melebarnya fosa posterior, pembesaran kistik ventrikel keempat, hipoplasia vermis serebelar, dan rotasinya ke atas. Kebanyakan pasien menderita hidrosefalus pada saat diagnosis.Presentasi kasus: Seorang wanita multipara berusia 36 tahun dengan usia kehamilan 39 minggu, pasien dari poliklinik kebidanan dengan rencana induksi persalinan. Pada pemeriksaan USG oleh bagian fetomaternal ditemukan kelainan kongenital pada janin yaitu adanya hidrosefalus disertai Dandy-Walker syndrome. Pasien menyangkal konsumsi alkohol, penggunaan obat-obatan kosmetik seperti isotretinoin atau obat pengencer darah. Pasien sebelumnya mengalami demam mendadak tanpa ruam kemerahan selama 7 hari pada usia kehamilan 6 bulan dan sembuh dengan sendirinya. Pasien mengaku memelihara kucing di rumahnya sejak tahun lalu. Pasien mengaku belum pernah memeriksakan darahnya untuk pemeriksaan TORCH. Setelah pematangan serviks dengan Misoprostol sesuai FIGO 25 mcg/PV/6 jam. Bayi perempuan lahir hidup, BW 2440 gr, BL 46 cm, A/S : 6/8.Kesimpulan: Pasien masuk RS dengan keluhan utama G4P3A0L3 Usia kehamilan 39-40 minggu, tidak bersalin dan janin hidup tunggal dalam kandungan, presentasi kepala pasien dari klinik kebidanan dengan episode muntah intermiten, sakit kepala dengan rencana induksi persalinan dengan hasil USG Sindrom Dandy-Walker. Keahlian yang cukup diperlukan dalam mendiagnosis dan mengobati malformasi yang disebabkan oleh Dandy Walker. Wanita hamil dengan DWS dalam pemeriksaan USG janin harus ditawarkan pemindaian USG janin yang cermat dan komprehensif serta pengujian genetik prenatal lebih lanjut.Kata kunci: Malformasi Dandy-Walker, kelainan kongenital, kehamilan, diagnosis prenatal